A gram-positive enhancer matrix particles vaccine displaying swine influenza virus hemagglutinin protects mice against lethal H1N1 viral challenge - Zhang, Yufei; Zhang, Pei; Du, Xiaoyue; Shi, Xiaona; Wang, Jinling; Liu, Shuying (Frontiers in Immunology, 2025)
IntroductionAnimal influenza viruses pose a danger to the general public. Eurasian avian-like H1N1 (EA H1N1) viruses have recently infected humans in several different countries and are often found in pigs in China, indicating that they have the potential to cause a pandemic. Therefore, there is an urgent need to develop a potent vaccine against EA H1N1.MethodsIn this study, we report the effective intramuscular (i.m.) and/or intranasal (i.n.) vaccination of mice with a subunit influenza vaccine utilizing safe adjuvant gram-positive enhancer matrix (GEM) particles derived from the food-grade bacterium Lactococcus lactis. The hemagglutinin (HA)-protein anchor (PA) subunit vaccine can be simply mixed with GEM particles to produce vaccines.ResultsAfter two booster injections, the i.m.+i.n. administered GEM subunit vaccine achieved hemagglutination inhibition titers in the serum that were equivalent to those observed using the conventional i.m. method. The mucosal and Th1-biased immune responses generated by the i.m. administered subunit vaccine alone were inferior to those induced by the i.n. and i.m.+i.n. administered subunit vaccines. Vaccinated mice were challenged with live viruses (G4 EA H1N1 and A/PR/8/34) to determine whether the adjuvant combination protected against the virus after vaccination with the influenza subunit vaccine. Compared to mice inoculated with HA alone, mice immunized with i.m.+i.n. or i.n. HA-PA-GEM displayed undetectable viral titers in the lungs, at 5 d after challenge.DiscussionOverall, this study not only offers other potential platforms for the generation of swine influenza vaccines, but also a theoretical foundation for vaccine vector platforms that can be utilized for future research on other infections.